THE USE OF DIFFERENT PRACTICE SYSTEMS IN FOREIGN LANGUAGE TEACHING - Rahmonova, Saodat (Журнал иностранных языков и лингвистики, 2023)
Our article is about how important it is to make training fun. In particular, when creating technical games in English lessons, care must be taken to ensure that these are interesting for the students, meet the learning needs, and are quickly accepted by the audience. The author emphasizes that every teacher must have a choice about the use of games, taking into account the abilities, interests, knowledge level, and aspirations of their students. Some games can be used to practice, listen, speak, teach, and develop language materials. Lexical, grammatical, phonetic, spelling, etc.